THE ROLE OF CENTRE FOR ISLAMIC THOUGHT AND EDUCATION (CITE): Correcting Negative Image of Islam, Spreading Moderate Islam in Australia - Nurdin, Ahmad Ali; Anwar, Rosihon; Qodim, Husnul; Rostandi, Usep Dedi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This paper discusses the participation of educational institution, Centre for Islamic Thought and Education (CITE) in promoting and campaigning moderate and tolerance Islam in Adelaide, Australia. The article also attempts to close reading of the discourse of moderate Islam itself to answer fundamental questions about what moderate Islam is, what CITE attempts to do, can do, and cannot be expected to do. This study is essential to fill the gap in the dearth literature discussing the role of educational institution in campaigning moderate Islam in Australia. This study was based on observation and interviews conducted with main figures of CITE and the staff members or the supporters of the group who actively involved in their activities in Adelaide, Australia. The result of the study shows that as an educational institution, CITE has significant roles in promoting moderate Islam and straightening negative image of Islam in the West.